2010
DOI: 10.1111/j.1524-4725.2010.01782.x
|View full text |Cite
|
Sign up to set email alerts
|

The Current State of Treatment of Adverse Reactions to Injectable Fillers

Abstract: We certainly need more evidence. Reporting positive and negative treatment outcomes is important to improve our knowledge regarding these reactions. Therefore, registries focusing on adverse reactions to injectable fillers and their treatment should be encouraged. The authors have indicated no significant interest with commercial supporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 43 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…For late-onset nodules or granulomas, intralesional steroids (betamethasone 5 mg/mL or triamcinolone 10–40 mg/mL for 10 days up to 4 weeks) can be considered, although care needs to be taken to avoid skin atrophy. 2 , 4 …”
Section: Recognition and Treatment Recommendations – Delayed Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…For late-onset nodules or granulomas, intralesional steroids (betamethasone 5 mg/mL or triamcinolone 10–40 mg/mL for 10 days up to 4 weeks) can be considered, although care needs to be taken to avoid skin atrophy. 2 , 4 …”
Section: Recognition and Treatment Recommendations – Delayed Eventsmentioning
confidence: 99%
“…For persistent cases, additional measures can include a series of injections of 5-fluorouracil (50 mg/mL) in combination with steroids and/or lidocaine (1:3), methotrexate, local tacrolimus, 2 , 4 , 49 cortivasol, allopurinol, colchicine, isotretinoin, imiquinod, 49 laser-assisted removal, 45 or ultimately excision by surgery as a last resort. 12 …”
Section: Recognition and Treatment Recommendations – Delayed Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adverse events (AE) to the different filler types have been reported, but their origin has been debated (Alijotas-Reig et al, 2010;Sperling et al, 2010;Alijotas-Reig & Garcia-Gimenez, 2011;Bachmann et al, 2011). Some have presumed the events to be due to a hypersensitivity inflammatory response to the fillers, whereas others have demonstrated that bacterial infection is the cause of AEs, at least to polyacrylamide gels (Christensen et al, 2005(Christensen et al, , 2013Bjarnsholt et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In a review of patients with complications entered in the Injectable Filler Safety Study, all participants improved whether they underwent treatment or not. 23 The Tyndall effect, or bluish discoloration, can be seen with HA injections (►Fig. 6).…”
Section: Complicationsmentioning
confidence: 99%